Transdermal Delivery of Biomacromolecules using Lipid-Like Nanoparticles. - Bello, Evelyn. (2017)
Abstract: The transdermal delivery of biomacromolecules, including proteins and nucleic acids, is challenging, owing to their large size and the penetration-resistant nature of the stratum corneum. Thus, an urgent need exists for the development of transdermal delivery methodologies. This research focuses on the use of cationic lipid-like nanoparticles (lipidoids) for the transdermal delivery of proteins, and establishes an in vitro model for the study. The lipidoids used were first combinatorially designed and synthesized; afterwards, they were employed for protein encapsulation in a vesicular system. A skin penetration study demonstrated that lipidoids enhance penetration depth in a pig skin model, overcoming the barrier that the stratum corneum presents. This research has successfully identified active lipidoids capable of efficiently penetrating the skin; therefore, loading proteins into lipidoid nanoparticles will facilitate the transdermal delivery of proteins. Membrane diffusion experiments were used to confirm the results. This research has confirmed that lipidoids are a suitable material for transdermal protein delivery enhancement.; Thesis (M.S.)--Tufts University, 2015.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Qiaobing Xu.; Committee: Ayse Asatekin, and Sameer Sonkusale.; Keywords: Biomedical engineering, and Nanoscience.